A preliminary study on body plasma level of nitric oxide in workers exposed to carbon disulfide - Jiang, X.; Jian, Le; Hu, D. (Chinese Medical Association, 2000)
OBJECTIVE: To study changes in body plasma level of nitric oxide (NO) in workers exposed to carbon disulfide (CS(2)) and its possible mechanism. METHODS: Plasma levels of NO and lipid peroxide (LPO) and activity of erythrocyte superoxide dismutase (Ery-SOD) were determined in the workers exposed and unexposed to CS(2) in a chemical synthetic fiber works. RESULTS: Level of NO was (43.28 +/- 19.83) and (50.07 +/- 21.01) micromol/L in high- and low-dose exposed groups, respectively, significantly lower than that in the control group, which was (70.66 +/- 26.83) micromol/L (P < 0.05). Activity of Ery-SOD was 4 832.21 u/g Hb and 3,520.80 u/g Hb in high- and low-dose exposed groups, respectively, significantly higher than that in the control group, which was 2,425.34 u/g Hb (P < 0.05). Level of LPO was 19.38 and 17.09 micromol/L in high- and low-dose exposed groups, respectively, significantly higher than that in the control group, which was 4.37 micromol/L (P < 0.05). CONCLUSION: Occupational long-term exposure to CS(2) could induce reduction of NO level in the body with its mechanism related to increase of super-oxygen cation O(2)(*-) induced by CS(2).